Systematic Lymphadenectomy and Oncological Outcomes of Women With Apparent Early-Stage Clear Cell Carcinoma of the Endometrium: A Multi-Institutional Cohort Study - Tian, Yong; Ran, Lin; Liu, Yi; Xu, Yu; Shen, Juan; Mi, Gong-sheng; Ke, Feng-mei (Frontiers in Oncology, 2022)
Objective The survival value of systematic lymphadenectomy for endometrial cancer is ambiguous and controversial. The current study aimed to evaluate the long-term survival role of combined pelvic and para-aortic lymphadenectomy in patients with presumed early-stage clear cell carcinoma of the endometrium. Methods Patients in three Chinese teaching hospitals who presented between 2012 and 2017 with apparent early-stage clear cell carcinoma of the endometrium and underwent surgical staging were selected. Patients who did and did not undergo systematic lymphadenectomy were identified and clinicopathological characteristics were compared. Disease-free survival and overall survival were evaluated following the generation of the Kaplan-Meier curves and the comparison using the log-rank test. A Cox proportional hazards model was employed to control for confounders. Results A total of 244 patients underwent systematic lymphadenectomy and 89 did not receive lymph node dissection. The demographic and baseline data were comparable between the two groups. The rate of disease-free survival at 5 years was 64.10% in patients who underwent systematic lymphadenectomy and 45.05% in patients who did not undergo lymphadenectomy. Patients who underwent systematic lymphadenectomy had better disease-free survival than those who did not receive lymphadenectomy (HR, 0.54. 95% CI, 0.38-0.76. P=0.000). The rate of 5-year overall survival was 68.87% in the lymphadenectomy group and 53.33% in patients who did not undergo systematic lymphadenectomy. Systematic lymphadenectomy was also associated with improved 5-year overall survival for women with presumed early-stage clear cell carcinoma of the endometrium (HR, 0.58. 95% CI, 0.39-0.85. P=0.005). After adjusting for confounders, systematic lymphadenectomy was still independently associated with improved disease-free survival and overall survival. Conclusion Patients with apparent early-stage clear cell carcinoma of the endometrium who underwent systematic lymphadenectomy had better long-term survival than those who did not undergo systematic lymphadenectomy.